UroVysion™ fluorescence in situ hybridization (FISH) possibly has a high positive rate in carcinoma of non-urothelial lineages - Ke, Chunjin; Liu, Xuguang; Wan, Jie; Hu, Zhiquan; Yang, Chunguang (Frontiers in Molecular Biosciences, 2023)
Background: Positive UroVysionTM fluorescence in situ hybridization (FISH) is generally considered as urothelial carcinoma (UC). We clarify if UroVysionTM FISH can be positive in carcinoma of non-urothelial lineages (CNUL), and verify the consistency of urine FISH and histological FISH in CNUL. Methods: All CNUL subjects detected using urine FISH assay due to haematuria from Tongji Hospital were screened. Meanwhile, 2 glandular cystitis and 2 urothelial carcinoma were served as negative or positive control. Paraffin-embedded tissue sections of all subjects were sent to the pathology department for histological FISH detection. Results: A total of 27 patients were included in this study, including 9 with adenocarcinomas, 11 with squamous cell carcinomas, and 7 with other tumour types. The overall positive rate in urine FISH was 64.00% (16/25) in patients with CNUL, 77.78% (7/9) in those with adenocarcinoma and 54.55% (6/11) in those with squamous carcinoma. There was a significant difference in the GLP p16 gene deletion rate between UC and CNUL (100% vs. 8.00%, P =0.017). Histological FISH results showed that the histological results of 19 patients were consistent with their urine FISH results, and only one patient with stage Ⅲa urachal carcinoma had inconsistent histological FISH results (positive) and urine FISH (negative) results. Conclusions: We demonstrated for the first time the application value of FISH in CNUL on urine samples. Positive urine FISH tests indicate not only UC, but also CNUL. UroVysionTM FISH possibly has a high positive rate in CNUL. CNUL and UC have different genetic changes shown by FISH.